Effects of photobiomodulation, photodynamic therapy, and hyperthermia on mouse liver mitochondria bioenergetics - Mezzacappo, Natasha Ferreira (2024)
Mitochondria, as essential organelles in mammalian cells, play a crucial role in various therapeutic approaches, including photobiomodulation (PBM), photodynamic therapy (PDT), and hyperthermia, which are the primary focus of this study. Despite their clinical significance, many fundamental aspects of how these therapies impact mitochondrial function remain poorly understood, making this an important area for research. Therefore, this study proposes an in vitro investigation to assess the effects of these therapeutic principles on the mitochondrial bioenergetics of mouse liver. To analyze the effects of PBM, high-resolution respirometry (HRR) was employed on isolated mitochondria to evaluate both the real-time and post-irradiation impacts of 635 nm laser irradiation. Mitochondrial swelling was also assessed. The effects of PDT at 635 nm on mitochondrial respiration and swelling were examined by irradiating isolated mitochondria in vitro under three distinct conditions: following the exogenous application of -aminolevulinic acid (ALA), after protoporphyrin IX (PpIX) application, and following ALA-induced PpIX mitochondrial synthesis in vivo. Time-dependent thermal changes in mitochondrial respiration were investigated for hyperthermia using cultured mouse hepatocytes and isolated mitochondria. The findings regarding PBM revealed that real-time analysis of 635 nm irradiation produced different outcomes compared to post-irradiation assessments; however, both approaches indicated an overall enhancement of mitochondrial inner membrane permeability. In the first PDT condition, an increased proton leak was observed upon ALA irradiation, suggesting enhanced ALA auto-oxidation and accelerated production of reactive oxygen species (ROS). When comparing mitochondrial respiration and swelling experiments following PDT with exogenous PpIX versus ALA-induced endogenous PpIX, it was noted that PDT caused more significant damage to the respiratory system with exogenous PpIX, which contradicted existing literature and may have been influenced by the chosen experimental conditions. Regarding hyperthermia, results differed between isolated mitochondria and hepatocytes. Hepatocytes exhibited greater damage when exposed to temperatures of 45 and 47 °C, resulting in decreased physiological respiration, inhibition of the phosphorylation system, likely damage to complex I, and the release of cytochrome C. In contrast, increased temperature and incubation time affected isolated mitochondria, leading to progressively impaired electron transport chain function, compromised phosphorylation system, increased proton leak, and uncoupled respiration, all contributing to diminished respiratory control. These findings highlight the significant role of cellular machinery in protecting mitochondria from thermal damage. Furthermore, the results underscore that both temperature and incubation time play critical roles in analyzing hyperthermia-induced effects. Overall, this study emphasizes that experimental design profoundly influences outcomes when investigating mitochondrial responses to these therapeutic techniques.